2019
DOI: 10.1016/j.cor.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-guided local search for the vehicle routing problem

Abstract: Local search suffices to compute high-quality solutions for routing problems in a short time• Large neighborhoods combined with a well-implemented pruning make local search effective• Problem-specific knowledge can help to guide the search more effectively• The heuristic scales well in problem-size and can be applied to problem variants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 35 publications
0
79
0
1
Order By: Relevance
“…Penalty is the indicator involving the feature i, which is the distance between customer location and other locations, and λ, a parameters to GLS, represents the relative value of penalties to control the information on the search process with respect to the actual solution cost. Arnold and Sörensen [2019] found that λ = 0.1 works well.…”
Section: Local Searchmentioning
confidence: 97%
See 1 more Smart Citation
“…Penalty is the indicator involving the feature i, which is the distance between customer location and other locations, and λ, a parameters to GLS, represents the relative value of penalties to control the information on the search process with respect to the actual solution cost. Arnold and Sörensen [2019] found that λ = 0.1 works well.…”
Section: Local Searchmentioning
confidence: 97%
“…We found the method to improve the operators in the steepest descent search strategy to avoid the local optima for reaching global optima as with the guided local search (GLS) algorithm [Kibly et al, 1999]. To probably improve the efficiency of the solutions in the search process, Guided local search (GLS) is an optimization technique which is an intelligent search algorithm that exploits information to guide the local search in avoiding the local optimum [Voudouris, 1997;Voudouris et al, 2010;Kilby et al, 1999;Arnold and Sörensen, 2019]. The GLS solution modifies action from local search by augmented cost function of minimizing the problem objective function with the cost function to a penalty term that was applied by a penalty vector p, where pi is the penalty value of feature i.…”
Section: Local Searchmentioning
confidence: 99%
“…It was initially proposed by [15] and later applied to CVRP by [16]. According to [17], this method is memory-based as it determines and penalizes "ineffective" edges by increasing its cost to a new * , = , + ,…”
Section: Guided Local Search (Gls)mentioning
confidence: 99%
“…It is capable of obtaining more solutions by escaping from the local minima in a wider solution space. Arnold et al [16] combined three powerful local search techniques, and implemented them in an efficient way. In their work, experiments have been made to determine how local search can be effec-tively combined with perturbation and pruning and how to guide the search to better solutions.…”
Section: Introductionmentioning
confidence: 99%